2022
DOI: 10.1002/hbm.25855
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of whole‐cerebrum resting‐state networks using ultra‐high resolution acquisition protocols

Abstract: Resting‐state functional magnetic resonance imaging (fMRI) has been used in numerous studies to map networks in the brain that employ spatially disparate regions. However, attempts to map networks with high spatial resolution have been hampered by conflicting technical demands and associated problems. Results from recent fMRI studies have shown that spatial resolution remains around 0.7 × 0.7 × 0.7 mm 3 , with only partial brain coverage. Therefore, this work aims to present a novel fMRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 81 publications
0
38
0
Order By: Relevance
“…Early attempts of layer-fMRI connectivity studies have been somewhat limited to relatively small field of views, constrained to individual brain systems (Polimeni et al 2010; Guidi et al 2020; Huber et al 2017; Huber, Finn, et al 2020). More recent advancements in data sampling approaches, MR-contrast generation strategies, and confidence of the laminar signal interpretability allowed proof-of-principle extensions of layer-fMRI connectivity to larger FOV (Sharoh et al 2019; Huber et al 2021; Deshpande, Wang, et al 2022; Pais-Roldán et al 2020; Yun et al 2022). In this work, we aim to help the layer-fMRI community in building tools to make such whole-brain layer-fMRI connectivity protocols usable for neuroscience application studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Early attempts of layer-fMRI connectivity studies have been somewhat limited to relatively small field of views, constrained to individual brain systems (Polimeni et al 2010; Guidi et al 2020; Huber et al 2017; Huber, Finn, et al 2020). More recent advancements in data sampling approaches, MR-contrast generation strategies, and confidence of the laminar signal interpretability allowed proof-of-principle extensions of layer-fMRI connectivity to larger FOV (Sharoh et al 2019; Huber et al 2021; Deshpande, Wang, et al 2022; Pais-Roldán et al 2020; Yun et al 2022). In this work, we aim to help the layer-fMRI community in building tools to make such whole-brain layer-fMRI connectivity protocols usable for neuroscience application studies.…”
Section: Discussionmentioning
confidence: 99%
“…This means that focusing on one specific frequency window is expected to provide results that are largely representative of functional connections at any other temporal scale. Ongoing work in combining the whole-brain layer-fMRI approaches with further advanced hardware (Feinberg et al 2022; Beckett et al 2022) and MR-reconstruction (Yun et al 2022) will become important to confirm this temporal invariance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, largely owing to a lack of methods to image the whole brain with high spatial resolution and sufficient coverage, the literature has focused on region-of-interest (ROI)-based network analysis (static or dynamic), disregarding the depth at which the connections take place in the cortex. Recently, novel highresolution fMRI sequences have allowed us not only to detect the connections between remote functionallydifferent areas but to do so with sub-millimetre resolution, enabling the evaluation of resting-state networks at multiple cortical depths (Huber et al, 2020, Yun and Shah, 2017, Yun et al, 2020, Yun and al., 2021, Pais-Roldán et al, 2020, Pais-Roldán et al, 2023, Yun et al, 2022. For instance, we have previously shown that, in healthy subjects, areas of the default mode network (DMN) are strongly correlated in the superficial layers, while the central executive control network (CEN) involves connections between deeper cortical territories (Pais-Roldán et al, 2023).…”
Section: Introductionmentioning
confidence: 97%